2020
DOI: 10.1002/dc.24442
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐guided fine‐needle aspiration cytology in the diagnosis of the gastrointestinal stromal tumor of the stomach

Abstract: BackgroundThis study aims to evaluate the usefulness of endoscopic ultrasound‐guided fine‐needle aspiration cytology (EUS‐FNAC) in the diagnosis of the gastric gastrointestinal stromal tumor (GIST).MethodsWe retrospectively investigated the efficacy and accuracy of EUS‐FNAC in the diagnosis of gastric GIST. Cytological smears and cytoblock sections including immunohistochemistry and mutational studies from patients diagnosed as gastric GISTs were retrieved.ResultsThirty patients (mean age 68.8 years, range 32‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…22 In addition, the reported accuracy of preoperative diagnosis of EUS-TA-CFNAN using 22 or 25G needles in surgically resected GSEL cases ranged from 81.8% to 96.0%. 14,15,25,26 Accuracy in this study was also high (97.3%). The reported adverse event rates were low (0-4.5%), 27 while in our series the corresponding rate was 0%.…”
Section: Discussionsupporting
confidence: 57%
“…22 In addition, the reported accuracy of preoperative diagnosis of EUS-TA-CFNAN using 22 or 25G needles in surgically resected GSEL cases ranged from 81.8% to 96.0%. 14,15,25,26 Accuracy in this study was also high (97.3%). The reported adverse event rates were low (0-4.5%), 27 while in our series the corresponding rate was 0%.…”
Section: Discussionsupporting
confidence: 57%
“…Endoscopic ultrasonography-guided fine-needle aspiration (EUS-FNA) has become increasingly used for the preoperative diagnosis of GIST due to the unique intramural or submucosal location of the tumor. [10][11][12][13] The diagnostic performances of EUS-FNA can be further enhanced by performing rapid on-site evaluation during the biopsy. [14][15][16] It has been reported that EUS-FNA has high sensitivity and diagnostic yield (88%-100%) with low incidences of complications including bleeding and infection (0%-2.6%).…”
Section: Introductionmentioning
confidence: 99%
“…17 Compared to the biopsy, EUS-FNA offers a safer and convenient option and thus has been incorporated into the routine practice. 13,18 Recently, the fine-needle core biopsy has gained interest in the diagnosis of GIST, because it increases tissue sampling yield, allowing for more extensive histologic workup. 19,20 However, FNA cytology still provides a comparable preoperative tumor sampling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations